Handbook of research on teacher education : enduring questions in changing contexts - Cochran-Smith, Marilyn; Feiman-Nemser, Sharon; McIntyre, D. John.; Association of Teacher Educators (New York : Routledge, 2008)
This third edition aims to stimulate a broad conversation about foundational issues; bring multiple perspectives to bear, including historical perspectives; provide new specificity to topics that have been undifferentiated in the past; and include diverse voices in the conversation.
Includes bibliographical references and indexes.
Keywords: Teachers -- Training of -- United States